Dissecting the metabolic phenotypes of innate immune cells in response to pathogens during early life and adulthood - D'Rozario, Zachary Jude (Nanyang Technological University, 2024)
The prognoses of infectious disease outcomes display an interesting age-dependent trend where children usually have milder conditions than adults. However, little information exists explaining the differences in immune response to pathogens across age. Immunometabolism is an emerging field demonstrating that the metabolism of immune cells regulates the potentiation of effected immune response. Therefore, this study aims to explore the metabolic profiles of innate immune cells in young and adult mice as we suspect that potential metabolic differences underly the differential immune responses observed. We used a flow cytometry-based technique called Single Cell ENergetic metabolism profiling by Translation inhibition (SCENITH) to profile the metabolism of bone marrow and spleen neutrophils and monocytes isolated from young and adult mice at steady state and upon simulated infection with bacterial lipopolysaccharide (LPS). Our results revealed distinct metabolic profiles in splenic neutrophils and monocytes, with increased glycolytic phenotypes observed in cells from adult. With no significant differences observed in immune cells from the bone marrow, we deduced that the splenic microenvironment plays a role in shaping an increasingly glycolytic phenotype of neutrophils and monocytes with time. These results serve as a basis to understand potential differences in immune response to pathogens across age.